Values of aesthetic and religiosity towards tourism attraction - Regeg, I Made; Triguna, Ida Bagus Gde Yudha; Winaja, I Wayan (International research journal of management, IT and social sciences, 2019)
The results of this study were values of aesthetic and religiosity ??at the location have implications for tourist visits, economy, arts, culture, education, and the dynamics of the people in Karangasem Regency, namely (1) Implications for tourist visits: increased visits during the last two years have increased 5.8%, (2) Implications for the economy: there have been an increase in community economics, (3) Implications for art culture: there has been an increase in cultural arts creativity, 4) Implications for education: there was educational creativity increasing religious spiritual strength, self-control, personality, intelligence, noble character, and skills needed for himself, society, nation and country (5) Implications for the dynamics of the ummah, namely: (1) the increase of the people to pray and the harmony between humans and the God and their manifestations, humans and humans, and their environment.